2007
DOI: 10.1016/j.jvs.2006.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of aortic graft infection by 18-fluorodeoxyglucose positron emission tomography combined with computed tomography

Abstract: Functional in vivo molecular imaging is provided with 18-fluorodeoxyglucose positron emission tomography (FDG-PET), which can detect cells with high glucose turnover. FDG-PET is an established imaging tool in oncology but has also been used in infectious and inflammatory diseases. PET combined with computed tomography (PET/CT) shows the metabolic activity with precise anatomic localization. More than 2000 scanners have now been installed worldwide, and with better availability, this hybrid method has the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 5 publications
1
25
0
1
Order By: Relevance
“…1,[28][29][30][31][32][42][43][44][45][46] Three recent studies summarized the role of PET/CT for the diagnosis of VGI. [30][31][32] Although there were variables in imaging techniques and patient selection among these studies and other studies, the sensitivity and specificity of PET/CT were similar to those reported with standard CT for the diagnosis of VGI [28][29][30][31][32]39,[43][44][45][46] (Table 1 1 ). PET/ CT may be less precise than conventional CT to identify the anatomic location of VGI.…”
Section: Intra-abdominal Vgisupporting
confidence: 65%
See 2 more Smart Citations
“…1,[28][29][30][31][32][42][43][44][45][46] Three recent studies summarized the role of PET/CT for the diagnosis of VGI. [30][31][32] Although there were variables in imaging techniques and patient selection among these studies and other studies, the sensitivity and specificity of PET/CT were similar to those reported with standard CT for the diagnosis of VGI [28][29][30][31][32]39,[43][44][45][46] (Table 1 1 ). PET/ CT may be less precise than conventional CT to identify the anatomic location of VGI.…”
Section: Intra-abdominal Vgisupporting
confidence: 65%
“…Perigraft fluid is usually reabsorbed within 3 months postoperatively, and perigraft air is usually absorbed within the first week or so, although it can persist for as long as 2 months postoperatively. 1,28,[37][38][39] Intra-abdominal VGI can occur many months to years after surgery and might not have the CT findings typically seen in early infection. 28,39,40 In these patients, MRI can be considered if the CT findings are inconclusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FDG-PET/CT imaging is used for diagnosis of mycotic aneurysms, aortic graft infections, and sometimes for evaluation of symptomatic aneurysms. [43][44][45] Increased FDG-uptake has been reported in symptomatic AAAs. 46 In an analysis of 12 asymptomatic AAAs with FDG-PET/CT imaging, no aneurysm wall-specific uptake could be identified in any patient.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Given the high metabolic activity of inflammatory cells, 18 F-FDG is also a useful marker for various active infectious and inflammatory processes (11)(12)(13), including reports of a high sensitivity in the diagnosis of vascular prosthetic infections (14,15). Hybrid 18 F-FDG PET/CT has established the role of 18 F-FDG imaging for the assessment of suspected vascular graft infection, providing accurate anatomic localization of the site of infection with subsequent improved specificity (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%